The Role of Social Context and Identity in Code-switching: A Study Based on the Academic Staff at Uva Wellassa University - Herath, H.M.D.N.; Abeyweera, G.H.; Samarasinghe, A.G.S.M.; Nayanahari, W.M.L.; Dissanayake, D.M.R.N.; Silva, R.R.P (University of Jaffna, 2025)
Code-switching is a dominant linguistic phenomenon that occurs in bilingual and multilingual settings. This study examines the process of code-switching among bilingual and multilingual individuals, about the social factors that influence their decision to switch codes in different social contexts. The fundamental objective of the study was to determine whether Code-switching has a relationship between personal identity and social context. Accordingly, the research objectives were to explore how bilinguals identify when to switch between codes in different social contexts and to examine the linguistic and social factors that influence code-switching among bilinguals. Accordingly, fifteen (15) bilingual members of the academic staff of Uva Wellassa University were selected as the sample. The sample falls under the purposive sampling method. All the participants were proficient in English, and Sinhala or Tamil was their mother tongue. A case study methodology was used to collect data. The participants were individually interviewed using semi-structured interviews. The data was analysed based on Gumperz’s Social Identity Theory. The findings show that the participants’ choice of language is tied to identity formation and social positioning. The participants revealed that apart from the workplace, when they attend places such as shopping malls, theatres, and meetings, and when dealing with strangers who are unaware of their identity, they switch to English from their mother tongue. They also mentioned that it gives them a sense of superiority and aids in dealing with difficult situations. It also allows them to exercise power and authority. In contrast, in less formal and intimate settings, they use their mother tongue. The data suggests that the participants switch codes from their mother tongue to English in situations where they feel that their identity is at stake. They do so as a marker of their educational and professional status. Based on Social Identity Theory, code-switching occurs as part of identity negotiation in social interactions. The participants’ switch to English, especially when they consider their identity to be at stake, shows an active negotiation of how they wish to be perceived in that context. By switching to English, participants aim to assert their position within a particular social group, showing capability and professionalism that their mother tongue might not convey. Accordingly, the researchers concluded that code-switching is not a mere linguistic choice based on convenience in communication but a social strategy used to navigate various societal expectations and self-perceptions. This study contributes to the field of sociolinguistics by revealing the relationship between language use, social context, and identity, specifically among bilingual individuals. Further studies could investigate the influence of other social variables, such as age and gender, on code-switching in similar contexts.
Keywords: Code-switching; Bilingualism; Social identity; Social context; Social positioning